Optimasi Proses Pembuatan Tepung Asap (Optimization Process For Production Of Smoke Powder) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Experiments were performed to optimize the process of smoke powder production using liquid smoke of coconut shell as raw material and rice powder as a model system for filler of smoke powder. The liquid smoke was produced by pyrolization method and the purification of the liquid smoke was done by redistillation method. The redistilled liquid smoke was diluted with varied water and mixed with some ratio of rice powder. The sensories of smoke powder was evaluated for ador, taste and overall, and the data were optinrzed using Response Surface Methodology. .The,result -of optimization process on the production of smoke powder indicated that the optimum temperature for redistillation process were 106 "C. the ratio of redistlled liquid smoke and rice powder was 2.5m11 50 gram, and the concentration of the liquid smoke was 15.1%. The confirmation of the optimization value indicated that the smoke powder was acceptable for consumer,